The Small Sample Effects of Various Treatments of Truncation Remainders in the Estimation of Distributed Lag Models - Schmidt, Peter (The Review of Economics and Statistics, 1975)
Peter Schmidt, The Small Sample Effects of Various Treatments of Truncation Remainders in the Estimation of Distributed Lag Models, The Review of Economics and Statistics, Vol. 57, No. 3 (Aug., 1975), pp. 387-389